Strategic leadership: realizing student aspiration outcomes - Zulkipli, Inas; Mohd Ali, Hairuddin (Partridge, 2018)
The synergy of academic affiliation between postgraduate student and her research supervisor was able to initiate and generate new and contemporary knowledge that will definitely enrich the relevant literature. Therefor this book is generated purely due to the contemporary knowledge that it contains.